Views of Muslim Scholars in Medan City on Zakat Institutions - Syahrial Hasanuddin Pohan; Hartato Rianto; Dyah Syafira (Yayasan Multidimensi Kreatif, 2024)
This research aims to analyze the practice of paying zakat, infaq, and alms conducted by university academics in Medan, referred to as Muslim scholars, and their perspectives on zakat management organizations. The study will delve into the relationship between the perspectives of university academic communities in North Sumatra on zakat management organizations and their practice of paying zakat, infaq, and alms. Additionally, this research will highlight the contribution of universities to the management of zakat, infaq, and alms in North Sumatra. The research employs a qualitative methodology. Data collection was carried out by distributing questionnaires to university communities in North Sumatra. The findings obtained from the field will be thoroughly explained, interpreted, and systematically organized to ensure clarity. The results reveal that the interaction between Muslim scholars and zakat institutions remains minimal. This is evident in the limited two-way engagement, where many Muslim scholars do not channel their zakat, infaq, and alms through zakat institutions, and conversely, zakat institutions often fail to involve Muslim scholars in managing zakat, infaq, and alms funds